2020
DOI: 10.1080/03007995.2020.1815685
|View full text |Cite
|
Sign up to set email alerts
|

Paramedical students’ perceptions of research: a survey

Abstract: Answering this questionnaire constitutes consent. We estimate it will take you 15 minutes on average. You can stop at any time and resume later, provided you have saved your answers.Your personal data will be processed by computer to enable us to analyze the results of the research with regard to the research objective. The categories processed are: your contact details and personal information, your feelings about the research and your skills. The people responsible for data processing are the coordinators, w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 14 publications
0
6
0
Order By: Relevance
“…Overall, the newly graduated paramedical professionals perceived themselves more as users than as generators of evidence. Research is also essentially perceived as patient centered; this should be considered in light of the fact that the main barrier to research was a preference for their core work [4]. This also concurs with the fact that nurses' satisfaction at work has been found to strongly correlate with thinking of their function in terms of "people-centered" care of patients [8], and the fact that research has been perceived as not being part of their culture [31].…”
Section: Professional Representations Of Researchmentioning
confidence: 69%
See 3 more Smart Citations
“…Overall, the newly graduated paramedical professionals perceived themselves more as users than as generators of evidence. Research is also essentially perceived as patient centered; this should be considered in light of the fact that the main barrier to research was a preference for their core work [4]. This also concurs with the fact that nurses' satisfaction at work has been found to strongly correlate with thinking of their function in terms of "people-centered" care of patients [8], and the fact that research has been perceived as not being part of their culture [31].…”
Section: Professional Representations Of Researchmentioning
confidence: 69%
“…In a previous study, we investigated the perceptions of research of paramedical students in their final year (speech therapy, occupational therapy, psychomotricity, audiometry, physiotherapy, orthoptics) through a national online survey conducted between January and March 2019 [4]. At the end of the survey, participating students were asked to provide their email address if they were happy to follow up with an interview in order to explore their perceptions in more depth.…”
Section: Participantsmentioning
confidence: 99%
See 2 more Smart Citations
“…Yet, Mc Curtin and Clifford (2015) show that young Irish professionals tend to seek advice from experienced professionals rather than use EBP. Lastly, the appropriation of EBP is still recent and extremely diverse among allied health professions, of which SLT is a part, and the general implementation must be accompanied by evolution in schools teaching rehabilitation; although students are reported to find research useful but not competent in this area (Decullier et al., 2020). Pagnamenta and Joffe (2018) surveyed the amount and nature of research training in courses for speech and language therapists in the UK; they found a high variability in training programmes, of the levels of perceived confidence of graduates, not only for active participation in research and for leading research, but also for research awareness.…”
Section: Introductionmentioning
confidence: 99%